Getting back to the “new normal”: Autonomy restoration during a global pandemic - ANICICH, Eric M. (Institutional Knowledge at Singapore Management University, 2020)
We investigate the psychological recovery process of full-time employees during the two-week period at the onset of the Coronavirus pandemic (COVID-19). Past research suggests that recovery processes start after stressors abate and can take months or years to unfold. In contrast, we build on autonomy restoration theory to suggest that recovery of impaired autonomy starts immediately even as a stressor is ongoing. Using growth curve modeling, we examined the temporal trajectories of two manifestations of impaired autonomy—powerlessness and (lack of) authenticity—to test whether recovery began as the pandemic unfolded. We tested our predictions using a unique experience-sampling dataset collected over a two-week period beginning on the Monday after COVID-19 was declared a “global pandemic” by the WHO and a “national emergency” by the U.S. Government (March 16-27, 2020). Results suggest that autonomy restoration was activated even as the pandemic worsened. Employees reported decreasing powerlessness and increasing authenticity during this period, despite their subjective stress-levels not improving. Further, the trajectories of recovery for both powerlessness and authenticity were steeper for employees higher (vs. lower) in neuroticism, a personality characteristic central to stress reactions. Importantly, these patterns do not emerge in a second experience-sampling study collected prior to the COVID-19 crisis (September 9-20, 2019), highlighting how the pandemic initially threatened employee autonomy, but also how employees began to recover their sense of autonomy almost immediately. The present research provides novel insights into employee well-being during the COVID-19 pandemic and suggests that psychological recovery can begin during a stressful experience.